2021
DOI: 10.1016/j.det.2021.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Manifestations of COVID-19 in the Inpatient Setting

Abstract: Synopsis Cutaneous findings have increasingly been reported in patients with coronavirus disease 2019 (COVID-19). This review discusses associated skin findings in COVID-19 patients in the inpatient setting, ranging from vasculopathy-related lesions associated with high hospitalization rate and poor prognosis to inflammatory vesicular and urticarial eruptions that are rarely associated with prolonged hospitalization. We also discuss other reported COVID-19 cutaneous manifestations such as Sweet's sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 80 publications
0
19
0
Order By: Relevance
“…Pernio-like acral lesions in COVID-19 patients mostly occur on the toes, are characterized by pink papule that develop into violaceous purpuric lesions and are linked to changes in dermal microvasculature resulting in edema and lymphocyte infiltration (Agnihothri and Fox, 2021). These lesions are not to be confused with skin manifestations observed in severe patients with acral livedoid eruptions and retiform purpura, which arise due to a systemic hypercoagulant state (Agnihothri and Fox, 2021;Do et al, 2021).…”
Section: Clinical Findings Of Endothelial Dysfunction In Covid-19 Pat...mentioning
confidence: 99%
“…Pernio-like acral lesions in COVID-19 patients mostly occur on the toes, are characterized by pink papule that develop into violaceous purpuric lesions and are linked to changes in dermal microvasculature resulting in edema and lymphocyte infiltration (Agnihothri and Fox, 2021). These lesions are not to be confused with skin manifestations observed in severe patients with acral livedoid eruptions and retiform purpura, which arise due to a systemic hypercoagulant state (Agnihothri and Fox, 2021;Do et al, 2021).…”
Section: Clinical Findings Of Endothelial Dysfunction In Covid-19 Pat...mentioning
confidence: 99%
“…A Spanish research team reported 375 cases of COVID‐19 with cutaneous manifestations during the early period of the COVID‐19 pandemic and divided them into categories of acral areas with vesicles or pustules (pseudo‐chilblain), vesicular eruptions, urticarial lesions, maculopapular eruptions, and livedo or necrosis 4 . Although the interaction between cutaneous changes and the COVID‐19 disease burden is not fully understood, reporting COVID‐19‐related cutaneous manifestations is important for physicians given their possible correlations with unrecognized medical complications with COVID‐19, especially in the inpatient setting 5 …”
Section: Introductionmentioning
confidence: 99%
“…It accounts for 11% to 47% of all dermatological cases related to COVID-19 ( Table 1 ) [ 23 , 48 ]. Additionally, retrospective studies and case series reported a higher rate of hospitalization (45% to 80%) in COVID-19 patients with morbilliform eruptions compared to COVID-19 patients without the rash [ 23 , 48 , 49 , 50 , 51 ].…”
Section: Covid-19 Specific Dermatological Manifestationsmentioning
confidence: 99%
“…Morbilliform rashes tend to occur concurrently or after the emergence of other COVID-19-related symptoms [ 23 ]. Morbilliform eruptions are associated with moderate to severe COVID-19 symptoms [ 23 , 49 , 52 , 53 ]. Among COVID-19 patients, the most common anatomical locations for morbilliform eruptions include the chest, abdomen, back, arms, and legs ( Figure 2 A–C) [ 23 , 50 , 52 , 54 ].…”
Section: Covid-19 Specific Dermatological Manifestationsmentioning
confidence: 99%